The Role of Artificial Intelligence In Research Writing: A Critical Analysis - Shah, Santosh (Journal of Universal College of Medical Sciences, 2024)
Artiﬁcial Intelligence (AI) has made a signiﬁcant impact on healthcare and its inﬂuence in the domain of academic and research writing is no exception. AI tools are increasingly being used by researchers, academics, and writers to enhance the quality, efﬁciency, and productivity of their research writing process. However, the integration of AI raises both promising opportunities and pressing challenges, particularly concerning academic integrity, citation practices, and the overall writing process. As AI keeps improving, it has the potential to completely transform how research is written, making the process faster, more accurate, and more ethical. However, researchers need to be aware of the ethical concerns surrounding AI, such as bias in the data, lack of transparency, and changes to who owns the work. As AI technology gets better, researchers will likely work more closely with AI, opening up new possibilities and challenges in academic research.